Remote Teaching and Teachers’ Wellbeing in Nepal During Covid-19: A Review - K. C., Rejina (Far Western Journal of Education, 2024)
Teachers’ wellbeing was impacted adversely in the pandemic, which brought school closure and social distancing everywhere. Abruptly, the academic institutions had to shift from physical to remote teaching by using various online platforms. The main purpose of this study is to explore and understand teachers’ experiences of remote teaching during COVID-19 pandemic. It aims to examine how the sudden change to online teaching impacted teachers’ wellbeing, their personal lives, and its impact on their students’ learning outcomes. The study is likely a qualitative research design, focusing on exploring teachers’ experience and perceptions which involves a comprehensive analysis and synthesis of existing literature, particularly based on the empirical studies related to remote teaching during the pandemic. It involves indentifying theme pattern, and insights related to teachers’ experience of remote teaching. It also sheds light on how teachers employed effective pedagogy as coping mechanism and explored the opportunities for learning new skills as their professional development amidst crisis.